ANALISIS POLA KOMUNIKASI MENGGUNAKAN MODEL VICS FLANDERS DALAM PEMBELAJARAN KIMIA DI SMA NEGERI 1 SUNGAI RAYA - Gilang Prastyca; Hairida Hairida; Maria Ulfah (EduChem, 2021)
Communication is the process of delivering messages from the communicator (source) to the communicant (receiver) through certain media to produce certain effects or goals by expecting feedback or reciprocity. The purpose of this study was to analyze the communication patterns carried out in chemistry learning at SMA Negeri 1 Sungai Raya. This research uses a descriptive method. The research subjects were chemistry subject teachers and students of class XI IPA 3 and XI IPA 4 SMA Negeri 1 Sungai Raya in the 2019/2020 school year. The instrument used to analyze teacher and student communication patterns is Matrix verbal interaction category system (VICS) Flander developed by Amidon and Hunter. The results showed that the communication patterns that occur are one-way communication patterns in which communication patterns are still discussed by the subject teacher